Fundamentals of growth, storage, genetics and microscopy of Aspergillus nidulans - Susan G W Kaminskyj (Fungal Genetics Reports, 2001)
This is a compendium of protocols for using Aspergillus nidulans in genetic, molecular, and cell biological investigations, originally written for members of my research group. It also summarizes our common growth media and nutritional supplements, many of which originally appeared elsewhere but now are difficult to locate. All solutions, tools, etc. are assumed to be sterile. All water should be sterile distilled or equivalent. Temperatures are in °C. Strains are available from the Fungal Genetics Stock Center (http://www.fgsc.net/).